Performance of granular columns in soft clay - Tan, Leong Chee. (2009)
Granular columns are frequently used in soft soils to increase the bearing capacity of soft soils, to reduce the settlement, and to accelerate the consolidation. The soil-column interaction depends on several parameters, such as the stiffness of the column material and of the soft soil, loading rate, area ratio and the drainage conditions for both column and soft soil. The main purpose of this study was to investigate the effect of the area ratio and the drainage conditions on the behavior of soft soil reinforced by granular columns.